POPULASI Corcyra cephalonica (LEPIDOPTERA;PYRALIDAE) PADA BEBERAPA KETEBALAN MEDIA TEPUNG JAGUNG - Sandy J. Laoh; Daysi Kandowangko; Jimmy Rimbing (Universitas Sam Ratulangi, 2017)
ABSTRACT This research was conducted at the Laboratory of Plant Pests and Diseases Faculty of Agriculture, University of Sam Ratulangi. Research time is less than four months from September until December, 2016. This research use corn flour as feed for C. cephalonica. The research compiled in a completely randomized design (CRD) and as treatment is the thickness of corn flour as feed for C. cephalonica. This experiment consisted of four treatment, which is 2 cm, 4 cm, 6 cm and 8 cm. each treatment was repeated of five times.Â The result showed that thickness media of corn flour 8 cm had an average population imago of C. cephalonica most low at 54.2 individuals, while the population is high was found in media thickness of corn flour 2 cm with an average of 60.6 individuals, then at the media thickness of 6 cm and 4 cm on average the population is almost the same individuals 80.2 and 80.0 individuals to a thickness of 4 cm.